从“乡约”分析论罗近溪的政教观 = Political and cultivation concepts of Luo Jin-xi from the analysis on his village covenants - 张丹璐 Zhang, Danlu (2012)
罗汝芳，字惟德，号罗近溪，是明中叶阳明后学泰州学派始祖王心斋的二传弟子，被誉为“泰州派中唯一特出者”。其理论除了继承孔孟的仁学及阳明心学，强调身心一体的“良知学”道德修为外，更以新的理论诠释孟子“赤子之心”之说，发展出“捧茶童子却是道”、“破除光景”等见解。 明朝初期，明高祖朱元璋有意恢复成周之治，通过制定俗称“老人制度”的乡约条规使民得教，更留有后为泰州学派所广为推崇的“圣谕六言”。为此，阳明曾亲手起草《南赣乡约》，用约法的形式约束民之恶习，以期达到借鉴之效。而王心斋极其重视“圣谕六言”，传至近溪时，他更是进一步将“圣谕六言”权威化，并极力将高祖的形象神圣化。值得考究的是，近溪之所以如此做，其真正目的究竟为何，是为了维护政权教化的合法性或只是利用其为自己的学说建立权威依据，或只是其传达孔孟学说的手段之一？同时，近溪也积极致力于讲学运动，在其任职地区制定乡约并大肆推广“圣谕六言”之余，更主张从自我实践觉悟“道”的重要性，并强调“现成良知”的工夫论。在个人修为方面，其类似“功过格”的日记习惯及对“静坐”工夫的重视，也可看出在近溪不完全排斥释老之学在思想实践上的帮助，不免被疑是“近禅”、“道学”之流。 此外，虽然儒、释、道三教合流是明末学说的一个趋向，然近溪援释道入儒，是遵循师道亦或是“觉民行道”的手段之一，与其积极付诸努力推广的君道是否有必然的联系，亦是本文研究重点。因此本文着重于通过乡约探索近溪的政教观，而从近溪乡约推行实践中所隐含佛道德色彩，亦可窥见晚明三教合流与政教关联之风潮。Luo Ru-fang (罗汝芳, Luo Ru-fang), who was named Wei-de(惟德, Wei-de), or otherwise known as Luo Jin-xi (罗近溪, Luo Jin-xi), is a member of the Tai-zhou Sect (泰州学派, Taizhou xuepai), a branch of the late Ming Yang-Ming philosophy movement. His learning was previously describes as “unique”, in the sense that other than inheriting traditional themes in the movement, Luo had proposed extensions based on new interpretations of Mencius’s classics. A seldom discussed but equally significant development, however, is Luo’s attitude towards the “Six Words from the Imperial Edict” (圣谕六言, shengyu liuyan) by Zhu Yuan-zhang (朱元璋, Zhu Yuan-zhang). During the early Ming era, in an effort to revive the golden age of Zhou dynasty, Zhu had promulgated the “Elderly Policy” (老人制度, laoren zhidu) as a means of moral education. A by-product from the edicts ordering this System in place was what later came to be known as the “Six Words from the Imperial Edict”. Philosophers from the Tai-zhou Sect, following Yang-Ming’s lead, had traditionally assigned great importance to these Six Words. Luo was no exception, but we see that Luo had pushed such significance to an extreme, drawing upon it as an ontological basis and a source of authority. Whether intended or not, such efforts have led to the immortalization of Zhu in Luo’s writings. This leads this paper questions Luo’s intentions in his efforts. Was it an effort to justify the government orthodoxy? Was it to lend credit to his philosophical innovations? Or was it merely a means of communicating Confucianism? On the other hand, we see that Luo had practiced Taoist conventions in cultivating the mind and body while preaching Confucianism. He had, for example, emphasized meditation and kept dairies on daily wrong doings (gong-guo ge). This reveals the synthetic nature of Luo’s learning; he is a Confucian who does not reject the practical benefits of Taoist and Buddhist conventions in cultivating the mind and body. Previous studies have pointed to the fact that such a synthetic nature of Neo-Confucianism is a product of times, in Luo’s case however, this paper wishes to explore his attitude towards the two “heretical” religions, i.e. Taoism and Buddhism. Was his adaptation of them a subconscious product inherited from his teacher? Or was it a conscious means of proselytization? Furthermore, is there an interaction between his intentions in adapting Taoism and justifying the government orthodoxy? These unanswered questions are critical towards understanding Luo as a philosopher of his time and thus warrants discussion.